The p-Anisaldehyde/β-cyclodextrin inclusion complexes as fumigation agent for control of postharvest decay and quality of strawberry. (December 2021) - Lin, Ying; Huang, Ran; Sun, Xiuxiu; Yu, Xi; Xiao, Ying; Wang, Ling; Hu, Wenzhong; Zhong, Tian
Abstract: In order to evaluate the potential of developed β-cyclodextrin (β-CD)/ p -Anisaldehyde (PAA) inclusion complexes as a fumigation agent for the postharvest decay control in strawberry, both in vitro and in vivo tests were conducted. According to the colony morphology analysis on PDA media, inclusion complexes showed activity on inhibiting the mycelial growth of the fungi including Rhizopus stolonifer, Aspergillus niger and Penicillium . The effect of inclusion complexes on controlling postharvest decay in fresh strawberry was also confirmed by in vivo test, in which the inclusion complexes-treated fruit displayed significantly lower incidence and severity than control, β-CD-treated and free PAA-treated fruit. Moreover, evaluations of fruit qualities including color, weight loss, firmness and TSS, as well as the sensory indexes including appearance, color, texture and flavor were carried out in turn, showing there was no significant difference between inclusion complexes-treated fruit and the other groups. Highlights: The p -Anisaldehyde/β-CD inclusion complex was used as a fumigation agent. The inclusion complex displayed in vitro activity against three common fungi. The inclusion complex reduced incidence and severity of the decay in strawberry. The inclusion complex maintained the fruit quality during storage.